2006
DOI: 10.1016/j.molcel.2006.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Cryptic Unstable Transcripts Is Directed by Yeast RNA-Binding Proteins Nrd1 and Nab3

Abstract: Studies of yeast transcription have revealed the widespread distribution of intergenic RNA polymerase II transcripts. These cryptic unstable transcripts (CUTs) are rapidly degraded by the nuclear exosome. Yeast RNA binding proteins Nrd1 and Nab3 direct termination of sn/snoRNAs and recently have also been implicated in premature transcription termination of the NRD1 gene. In this paper, we show that Nrd1 and Nab3 are required for transcription termination of CUTs. In nrd1 and nab3 mutants, we observe 3'-extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
251
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(258 citation statements)
references
References 51 publications
6
251
0
1
Order By: Relevance
“…Alternatively, the recruitment of the exosome could be constitutive and independent of specific processing events. For instance, the degradation of cryptic unstable transcripts in S. cerevisiae is closely coupled to the Nrd1p-Nab3p-dependent transcription termination pathway (Arigo et al, 2006;Thiebaut et al, 2006). Our results suggest, in contrast, that protein-coding genes in insects are monitored by a constitutive mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…Alternatively, the recruitment of the exosome could be constitutive and independent of specific processing events. For instance, the degradation of cryptic unstable transcripts in S. cerevisiae is closely coupled to the Nrd1p-Nab3p-dependent transcription termination pathway (Arigo et al, 2006;Thiebaut et al, 2006). Our results suggest, in contrast, that protein-coding genes in insects are monitored by a constitutive mechanism.…”
Section: Discussionmentioning
confidence: 76%
“…These transcripts are estimated to originate from 10% of yeast intergenic regions (Wyers et al 2005; although see Neil et al 2009 andXu et al 2009). After Nrd1-dependent termination by RNAPII, CUTs are rapidly polyadenylated by the TRAMP complex, and then degraded by the nuclear exosome (Wyers et al 2005;Arigo et al 2006b;Houalla et al 2006;Thiebaut et al 2006). Recently, Gudipati et al (2008) showed that Nrd1-dependent termination of CUTs is inhibited by CTD phosphorylation on Ser2 and promoted by Ser5 phosphorylation.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…Non-coding RNAs found upstream of known protein coding genes in yeast are termed cryptic unstable transcripts (CUTs). Both the Nrd1/Nab3/Sen1 complex, which binds CUTs in a sequence dependent manner, 14 and modification of CUTs by addition of a short polyA tract by the Trf-Air-Mtr4 polyadenylation (TRAMP) complex activate exosome-mediated degradation. 15,16 This exosome-dependent degradation explains why the CUTs are rarely seen in genomic assays.…”
Section: Divergent Transcription In Mammalsmentioning
confidence: 99%